P2Y purinergic receptor signaling in oral squamous cell carcinoma cell lines and its role in proliferation and cisplatin-mediated apoptosis - Lok, Mun Law; Norazrina Azmi,; Paterson, Ian Charles; Ng, Pei Yuen (Penerbit Universiti Kebangsaan Malaysia, 2022)
Treatment of advanced stage oral squamous cell carcinoma (OSCC) often involves the use of chemotherapeutic agents, such as cisplatin. However, its use often results in therapeutic failure due to chemoresistance. This study focused on a class of purinergic receptors, namely P2Y, which are activated via interaction with extracellular nucleotides. The functional effects of P2Y receptor activation in OSCC cell lines as well as the signaling pathways involved were investigated. The expression of P2Y2 receptors in histological sections of OSCC was studied due to its association with cancer. Activation of MAPK pathways via extracellular nucleotides were studied in OSCC cell lines, along with downstream effects such as proliferation and cisplatin-mediated apoptosis. Immunohistochemical staining of OSCC tissue samples showed loss of P2Y2 expression as the disease progressed. Western blotting identified different MAPK signaling pathways were activated by extracellular nucleotides. Bromodeoxyuridine proliferation assays showed increased cellular proliferation in the OSCC cell lines H400 (p < 0.001) and SAS (p < 0.001) after 24 h treatment with ATP. However, the ability of extracellular nucleotides to activate multiple P2Y receptor subtypes may indicate the involvement of other subtypes aside from P2Y2. Cisplatin-mediated apoptosis was enhanced in SAS cells co-treated with ATP (p < 0.001), while H376 (p < 0.001) showed reduction in the number of apoptotic cells and no significant changes were observed in H103. This study concluded that extracellular nucleotide on OSCC cell lines with different characterizations had varied downstream effects, which suggests the use of targeted therapy to specific individuals.